Analysis of Pteridophyta Plants Vegetation in Amporiwo Forest Area, Poso District - Nining Kasim Muhdin; Dewi Purwasih Samela; Fadhillah Nur Azizah (Jurnal Biologi Tropis, 2025)
Another role of ferns is as a source of plasma nutfah and also has the potential as a source of food and medicine. Analysis of pteridophyta plant vegetation aims to describe the types of Pteridophyta plants in the Amporiwo forest area. The type of research used in this study is a qualitative approach. The population and samples in this study were all types of ferns found in the Amporiwo forest area. Data analysis used a google lens camera and a reference book on Identification of Ferns (Pteridophyta). The results of the study showed that there were types of ferns (pteridophyta) with details of 5 orders, 9 families and 17 species, namely Pyrrosia lanceolata, Phymatosorus scolopendria. Pyrrosia piloselloides, Diplazium esculentu., Drynaria quercifolia, Christella leveille, Thelypteris pectiniformis, Asplenium nidus L., Nephrolepis biserrata, Pteridium esculentum, Dicranopteris linearis, Stenochlaena palustris, Dyplazium sorgonens, Ligodium palmatum, Lycopodiella cernua, Hipoderris brownie, Asplenium Polyodon. The conclusion is that the types of Pteridophyta plants in the Amporiwo forest area were found to be 5 orders, 9 families, and 17 species.